(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Football Club Community Trusts (FCCTs) attached to professional football clubs in the United Kingdom use their sport brand to engage young people in physical activity and support mental health. These interventions have expanded nationwide, yet their feasibility and acceptability remain under-researched. Guided by the Medical Research Council and National Institute for Health and Care Research Framework for Developing and Evaluating Complex Interventions, this study explores stakeholders’ views to identify key features for successful delivery and areas for refinement. Methods: This qualitative study examined the perspectives of staff and young people involved in mental health-focused interventions across five FCCTs in the English Football League. Semi-structured interviews were conducted with 17 staff members managing or delivering the interventions, and focus groups were held with 19 young participants. Stakeholders engaged in various interventions, such as MENTalk, Safety Nets, and the Premier League-funded Inspires programme. Reflexive thematic analysis was used to analyse the data. Results: Staff and young people identified five key features of effective programmes: (1) the appeal of the professional club brand, (2) opportunities to play football, (3) using sports-based examples to teach mental health concepts, (4) relatable facilitators as role models, and (5) encouraging open discussions around mental health. Suggested refinements included (1) sustaining participant engagement and (2) increasing interactive activities. Conclusion: This study provides insight into what makes mental health-focused FCCT interventions acceptable and engaging for young people. Stakeholders highlighted the importance of football-based delivery, relatable models, and open dialogue around mental health. These findings offer practical recommendations for enhancing the design and delivery of FCCT and similar sports-based programmes aimed at supporting young people’s mental wellbeing. Support/Funding Source: The author received no financial support for this research.